Forty-two years of responding to Ebola virus outbreaks in Sub-Saharan Africa: a review. Issue 3 (8th March 2020) - Rugarabamu, Sima; Mboera, Leonard; Rweyemamu, Mark; Mwanyika, Gaspary; Lutwama, Julius; Paweska, Janusz; Misinzo, Gerald
Abstract : Introduction: Ebola virus disease (EVD) is one of the deadliest haemorrhagic fevers affecting humans and non-human primates. Thirty-four outbreaks have been reported in Africa since it was first recognised in 1976. This review analysed 42 years of EVD outbreaks and identified various challenges and opportunities for its control and prevention in Sub-Saharan Africa. Methods: A literature search of relevant articles on EVD was done in PubMed, Web of Science and Google Scholar electronic databases. Articles published from 1976 to 2019 were reviewed to document reports of EVD outbreaks in Sub-Saharan Africa. Data extraction focused on the year of outbreak, geographical spread, virus strain involved, number of cases and deaths, case fatality, and outbreak management. Analyses of trends in case fatality were performed by calculating ORs between times. Results: In the past four decades, a total of 34 EVD outbreaks affecting 34 356 cases and causing 14 823 deaths were reported in 11 countries in Sub-Saharan Africa. The overall case fatality rate (95% CI) was 66% (62 to 71) and did not change substantially over time (OR in 2019 vs 1976=1.6 (95% CI 1.5 to 1.8), p<0.001). The results of this review indicate that challenges to control EVD outbreaks are related to epidemiological, sociocultural and health system factors. Conclusions: Sub-Saharan Africa continues to face considerable challenges in EVD control, whereby there are no significant changes in case fatality rates observed during the past four decades. Socioeconomic and cultural processes need to be critically considered to shape the community behaviours that lead to exposure to EVD outbreaks. Areas that need to be addressed to prevent future EVD outbreaks include a broad-based, one-health approach, effective communication, social mobilisation, and strengthening of the health systems.